Effect of fermentation, malting and ultrasonication on sorghum, mopane worm and Moringa oleifera: improvement in their nutritional, techno-functional and health promoting properties - Maleke, Mpho Sebabiki; Adebo, Oluwafemi Ayodeji; Wilkin, Jonathan; Ledbetter, Moira; Feng, Xi; Gieng, John; Molelekoa, Tumisi Beiri Jeremiah (Frontiers in Nutrition, 2024)
Background: Food processing offers various benefits that contribute to food nutrition, food security and convenience. This study investigated the effect of three different processes (fermentation, malting and ultrasonication) on the nutritional, techno-functional and health-promoting properties of sorghum, mopane worm and Moringa oleifera. Methods: The fermented and malted flours were prepared at 35 °C for 48 hours, and for ultrasonication, samples were subjected to 10 minutes at 4 °C with amplitudes of 40 - 70 Hz. The biochemical, nutritional quality and techno-functional properties of the obtained flours were analyzed using standard procedures. Results: Fermentation resulted in significantly lower pH and higher titratable acidity in sorghum and mopane worm (4.32 and 4.76; 0,24 and 0,69 % lactic acid, respectively), and malting resulted in higher total phenolic content and total flavonoid content in sorghum (3.23 mg GAE/g and 3.05 mg QE/g). Ultrasonication resulted in higher protein and fibre in raw sorghum flour (13.38 and 4.53%) and mopane worm (56.24 and 11.74%) while raw moringa had the highest protein (30.68%). Biomodification by fermentation in sorghum led to higher water and oil holding capacity and increased dispersibility in the ultrasonicated samples. Ultrasonication of mopane worms led to higher water holding capacity, oil holding capacity and dispersibility. Lightness was found to be significantly higher in the fermented samples in sorghum and mopane worm. Raw moringa had the greatest lightness compared to the ultrasonicated moringa. Moringa had the most redness and browning index among all samples. Conclusion: In this study, all the investigated processes were found to have caused variations in flours' biochemical, nutritional and techno-functional properties. Ultrasonication process was noteworthy to be the most efficient to preserve the nutritional value in sorghum, mopane worm and M. oleifera flours.